In Capra's Shadow : The Life and Career of Screenwriter Robert Riskin - Scott, Ian, 1954- (Book collections on Project MUSE., 2006)
Because screenwriter Robert Riskin spent most of his career collaborating with legendary Hollywood director Frank Capra, Riskin's own unique contributions to film have been largely overshadowed. With five Academy Award nominations to his credit for such monumental films as Lady for a Day, Mr. Deeds Goes to Town, You Can't Take It with You, Here Comes the Groom, and It Happened One Night (for which he won the Oscar), Riskin is often imitated but rarely equaled. In Capra's Shadow: The Life and Career of Screenwriter Robert Riskin is the first sociohistorical analysis of the Hollywood pioneer's l.